Policies and procedures for evaluation and approval of schools of nursing / nursing education programmes in the Commonwealth Caribbean (PAHO/WHO Washington, DCUS)
Presents policies and procedures to be used to assess and evaluate schools and nursing education programmes and to approve schools of nursing in the Caribbean.
Keywords: NURSES